A comparative study into the effects of venous and arterial blood on clot microstructure in critically unwell patients. Assessment of the diagnostic potential of a biomarker of haemostasis. (May 2023) - Pillai, Suresh; Evans, Vanessa; Davies, Gareth; Lawrence, Matthew J; Whitley, Janet; Battle, Ceri E; Williams, Phylip R; Morris, Keith; Evans, Phillip A
Blood for coagulation analysis can be sampled from the arterial or venous system in intensive care units (ICU). The determination of clot microstructure and strength by fractal analysis (d f ) gives valuable information in a range of vascular haemostatic disease and sepsis. We aimed to determine if d f could be measured equally and comparatively in arterial or venous blood, and 45 critically ill patients in an ICU were recruited. d f was found to be readily measured in arterial blood with results comparable to those in venous blood and that add value of d f as a potential marker of haemostasis in these patients.